As representações críticas da homofobia nas narrativas Em nome do desejo, de João Silvério Trevisan, e Brokeback mountain, de Annie Proulx - Gil, Frederic Grieco Deij Moral (2022)
In this thesis, I comparatively study the theme of homophobia in the novel Em nome do desejo (In the name of desire), by the Brazilian writer João Silvério Trevisan (1985), originally published in 1983, and in the short story Brokeback Mountain, by the American writer Annie Proulx (2003, 2006), whose first version was published in The New Yorker in 1997. I defend the hypothesis that these narratives engender critical representations of homophobia and the Western hegemonic ideal of masculinity. Therefore, I aim to analyze the configurations of these representations, mainly taking into account the homoerotic relationship between the characters João/Tiquinho and Abel Rebebel, in the novel Em nome do desejo, and Ennis del Mar and Jack Twist, in the short story Brokeback Mountain. This work of comparative literature adopts a stance of cultural critique, having as its central point a reflection on the precariousness of the lives of homoerotically inclined subjects in a profoundly homophobic culture like ours. Thus, given the aforementioned thematic axis, the relationship between literature, history, and society is extensively addressed throughout the thesis by drawing on reflections prompted by Eve Kosofsky Sedgwick (1985, 2007), Jurandir Freire Costa (1992), Michel Foucault (1999, 2012, 2014, 2015, 2016), Didier Eribon (2008), Georges Bataille (2014), Daniel Borrillo (2016), Judith Butler (2016, 2019a, 2019b), and other authors. The concepts of disciplining bodies, heterosexism, gender performativity, homophobia, social dispositifs, homoeroticism, and homoerotic closet are fundamental for the hermeneutic development of this literary study.